Review of the millipede genus Sibiriulus Gulička, 1972, with descriptions of three new species from Altai, Siberia, Russia (Diplopoda, Julida, Julidae) - Mikhaljova, Elena V.; Nefediev, Pavel S.; Nefedieva, Julia S.; Sakhnevich, Miroslava B.; Dyachkov, Yuri V. (Zootaxa, 2014)
The genus Sibiriulus Gulička, 1963, which has hitherto been known to comprise only four species, is rediagnosed and shown to include seven species from Siberia, Russia. Three species are described here as new to science: S. latisupremus sp. nov., S. baigazanensis sp. nov., S. aktashensis sp. nov. The species Sibiriulus profugus (Stuxberg, 1876) is recorded in the fauna of the Altai Province and the Republic of Altai for the first time. All currently known species of Sibiriulus are keyed and mapped, including the new species.